PARTIAL HANGING-UNUSUAL FINDINGS-A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2013)
A male patient was admitted to Bharati hospital Pune with alleged history of hanging. Ligature mark was seen on the neck and was going upwards on one side. Whenever there is a case of asphyxia due to ligature and no history available, the first question police ask a Forensic expert is whether it is hanging or strangulation? As we all know hanging is usually suicidal and strangulation is homicidal. Examination of ligature mark on neck is very useful to differentiate whether it is hanging or strangulation. But a medico-legal expert does not rely only on ligature mark to decide the manner of death. The case discussed here has characteristics of ligature mark similar to that in strangulation. It is very important that the Forensic expert considers all findings before arriving to a diagnosis of hanging/strangulation or suicidal/ homicidal.
Keywords: Hanging; Strangulation